Prevalence of congenital abnormalities on routine ultrasound scan of second and third trimester pregnancy - Mahela, Sangita; Talukdar, Bharat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Objective of the study was to evaluate the antenatal prevalence of major congenital abnormalities and its pattern. Methods: This is a cross-sectional study carried out in the department of ‘Radiology’ at ‘Fakhruddin Ali Ahmed Medical College and Hospital’, Barpeta. Patients in the 2nd and 3rd trimester of pregnancy, referred to ‘Radiology’ department from the outpatient and inpatient departments of ‘Obstetrics and Gynaecology’ were included in the study. Antenatal ultrasound findings were statistically analyzed on structured data collection form. Results: Total 2650 numbers of 2nd and 3rd trimester prenatal ultrasonography (USG) were done. Out of these 45 numbers of congenital anomalies were detected. The antenatal prevalence of congenital anomalies was 1.73%. The mean maternal age and mean gestational age at diagnosis was 25.5 years (SD ± 6.15) and 27 weeks (SD±6.42) respectively. Central nervous system (CNS) defect was the commonest (42%), of which maximum number had anencephaly defect i.e. 8 (17.78%) cases. Conclusions: Antenatal ultrasound is a non–invasive highly sensitive, accurate and cost effective imaging technique which gives good results in experienced hands. It is recommended that the obstetricians should advise regular USG at least at 2nd trimester.